Mechanism of a Novel Camptothecin-Deoxycholic Acid Derivate Induced Apoptosis against Human Liver Cancer HepG2 Cells and Human Colon Cancer HCT116 Cells - Xiao, Linxia; Xu, Jialin; Weng, Qi; Zhou, Leilei; Wang, Mengke; Liu, Miao; Li, Qingyong (Recent Patents on Anti-Cancer Drug Discovery, 2019)
Background: Camptothecin (CPT) is known as an anticancer drug in traditional Chinese medicine. However, due to the lack of targeting, low solubility, and instability of CPT, its therapeutic applications are hampered. Therefore, we synthesized a series of CPT-bile acid analogues that obtained a national patent to improve their tumour-targeting chemotherapeutic effects on liver or colon cancers. Among these analogues, the compound G2 shows high antitumor activity with enhanced liver targeting and improved oral absorption. It is significant to further investigate the possible anticancer mechanism of G2 for its further clinical research and application. Objective: We aimed to unearth the anticancer mechanism of G2 in HepG2 and HCT116 cells. Methods: Cell viability was measured using MTT assay; cell cycle, Mitochondrial Membrane Potential (MMP), and cell apoptosis were detected by flow cytometer; ROS was measured by Fluorescent Microplate Reader; the mRNA and protein levels of cell cycle-related and apoptosis-associated proteins were examined by RT-PCR and western blot, respectively. Results: We found that G2 inhibited cells proliferation of HepG2 and HCT116 remarkably in a dosedependent manner. Moreover, G2-treatment led to S and G2/M phase arrest in both cells, which could be elucidated by the change of mRNA levels of p21, p27 and Cyclin E and the increased protein level of p21. G2 also induced dramatically ROS accumulated and MMP decreased, which contributed to the apoptosis through activation of both the extrinsic and intrinsic pathways via changing the genes and proteins expression involved in apoptosis pathway in both of HepG2 and HCT116 cells. Conclusion: These findings suggested that the apoptosis in both cell lines induced by G2 was related to the extrinsic and intrinsic pathways.
Keywords: Anticancer effect